Venom from Anemesia species of spider modulates high voltage-activated Ca2+ currents from rat cultured sensory neurones and excitatory post synaptic currents from rat hippocampal slices - Kalikulov, D; Ayar, A; Nuritova, F; Frenguelli, BG; McClelland, D; Martin, DJ; Scott, RH (Churchill Livingstone, 2001)
The actions of crude venom from Anemesia species of spider were investigated in cultured dorsal root ganglion neurones from neonatal rats and hippocampal slices. Using mass spectrometry (MALDI-TOF MS), 10-12 distinct peptides with masses between about 3 and 10 kDa were identified in the crude spider venom. At a concentration of 5 mug/ml crude Anemesia venom transiently enhanced the mean peak whole cell voltage-activated Ca2+ current in a voltage-dependent manner and potentiated transient increases in intracellular Ca2+ triggered by 30 mM KCI as measured using Fura-2 fluorescence imaging. Additionally, 5-8 mug/ml Anemesia venom increased the amplitude of glutamatergic excitatory postsynaptic currents evoked in hippocampal slices. omega -Conotoxin GVIA (1 RM) prevented the increase in voltage-activated Ca2+ currents produced by Anemesia venom. This attenuation occurred when the cone shell toxin was applied before or after the spider venom. Anemesia venom (5 mug/ml) created no significant change in evoked action potentials but produced modest but significant inhibition of voltage-activated K+ currents. At a concentration of 50 mug/ml Anemesia venom only produced reversible inhibitory effects, decreasing voltage-activated Ca2+ currents. However, no significant effects on Ca2+ currents were observed with a concentration of 0.5 mug/ml. The toxin(s) in the venom that enhanced Ca2+ influx into sensory neurones was heat-sensitive and was made inactive by boiling or repetitive freeze-thawing. Boiled venom (5 mug/ml) produced significant inhibition of voltage-activated Ca2+ currents and freeze-thawed venom inhibited Ca2+ transients measured using Fura-2 fluorescence. Our data suggest that crude Anemesia venom contains components, which increased neuronal excitability and neurotransmission, at least in part this was mediated by enhancing Ca2+ influx through N-type voltage-activated Ca2+ channels. (C) 2001 Harcourt Publishers Ltd.
Keywords: Cerebellar Granule Neurons; Omega-Conotoxin Gvia; Calcium Channels; Inhibition; Toxin; Polyamine; Release; Ligand; Block